Glycolysis in tumor microenvironment as a target to improve cancer immunotherapy - Xiao, Chu; Tian, He; Zheng, Yujia; Yang, Zhenlin; Li, Shuofeng; Fan, Tao; Xu, Jiachen; Bai, Guangyu; Liu, Jingjing; Deng, Ziqin; Li, Chunxiang; He, Jie (Frontiers in Cell and Developmental Biology, 2022)
Cancer cells and immune cells all undergo remarkably metabolic reprogramming during the oncogenesis and tumor immunogenic killing processes. The increased dependency on glycolysis is the most typical trait, profoundly involved in the tumor immune microenvironment and cancer immunity regulation. However, how to best utilize glycolytic targets to boost anti-tumor immunity and improve immunotherapies are not fully illustrated. In this review, we describe the glycolytic remodeling of various immune cells within the tumor microenvironment (TME) and the deleterious effects of limited nutrients and acidification derived from enhanced tumor glycolysis on immunological anti-tumor capacity. Moreover, we elucidate the underlying regulatory mechanisms of glycolytic reprogramming, including the crosstalk between metabolic pathways and immune checkpoint signaling. Importantly, we summarize the potential glycolysis-related targets that are expected to improve immunotherapy benefits. Our understanding of metabolic effects on anti-tumor immunity will be instrumental for future therapeutic regimen development.